The concepts information and communication: perspectives from the academic communities of information, communication and computer engineering sciences (Perspectivas em Ciência da Informação, 2019)
Abstract We present an exploratory research that took place between 2013 – 2015, focusing on the perceptions regarding Information and Communication of fourteen PhD investigators, in two interdisciplinary centers in Brazil and Spain. This research is part of a new line of investigation initiated in 2014 by the Research Group: The concepts ‘Information’ and ‘Communication’ from the perspectives of several disciplines (Communication, Information Science and Computer Engineering) – CIC, in the Faculty of Information and Communication (FIC) of the University of the Republic, Uruguay. The dimensions of analysis defined to study the perceptions of the academicians are: academic formation, approaches to the Information and Communication concepts; similarities and differences between such concepts and theoretical references. The research strategy is based upon qualitative methods focused on in-depth interviews with qualified informants. Interviews were recorded in Spanish and Portuguese and transcribed into Spanish. A qualitative analysis was conducted by means of systematic techniques including content analysis of the discourse as well as reading and interpretation of the content which was presented in the corpus of the interviews. The perceptions of the academicians were categorized according to the disciplinary fields to which they belonged. General and specific conclusions about tendencies are presented, both supporting the need to promote reflection and debate in the interdisciplinary scientific community, focusing on the concepts of Information and Communicati